Changing minds and brains : the legacy of Reuven Feuerstein : higher thinking and cognition through mediated learning - Feuerstein, Reuven; Falik, Louis H.; Feuerstein, Refael S. (Teachers College Press, Columbia University, 2015)
"Decades before educators began to draw teaching and learning implications from neuroscientists groundbreaking findings on brain plasticiy, Reuven Feuerstein had already theorized it and developed practices for teaching and developing higher level cognition and learning for all students, even those with Down syndrome and other learning disabilities. His mediated learning, enrichment instruments, and dynamic assessment are used in urban districts in the United States and around the world to raise student achievement, success levels, and self-regulation"- Resumé vydavatel
Keywords: Feuerstein, Reuven, 1921-2014; myšlení; instrumentální obohacování (metoda); učení; thought and thinking; instrumental enrichment; learning; elektronické knihy; monografie; electronic books; monographs